Analisis Tiga Dimensi Short Video Marketing Yang Mempengaruhi Purchase Intention Generasi Z - Meyliana Tjan Mulyadi; Nur Laili Isnawati; Catharina Aprilia Hellyani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Short videos are videos that are five seconds to five minutes long. Short video marketing is now popular because it is considered interesting and interactive. This research was conducted to analyze the dimensions in short video marketing that influence generation Z's purchase intention, the dimensions used are the Emotional, Entertain, and Informative dimensions. The research method that used is literature study. The results showed that the emotional dimension has a significant effect on purchase intention, while the entertain dimension and informative dimension do not directly affect purchase intention but still must be considered.